1995
DOI: 10.1007/bf01323243
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Venezuelan equine encephalitis virus in mice olfactory tract

Abstract: Spread of Venezuelan equine encephalitis (VEE) virus and damage of the central nervous system (CNS) in mice infected by respiratory route was studied. Virus concentration in organs and blood, "dose-effect" relationships, and ultrastructural lesions in various tissues were examined in immune and normal mice. We showed, via three independent methods--characteristic curve investigations, tissue virus concentration dynamics, and ultrastructural methods--the spread of VEE virus through the olfactory tract into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 16 publications
0
45
0
1
Order By: Relevance
“…Previous studies have demonstrated that the murine model is characterized by biphasic disease, which starts with the productive infection of lymphoid tissue and ends in the destruction of the CNS by viral replication and a "toxic" neuroinflammatory response (12,13,15,16,39,42,43). By the time encephalitis has developed in an infected mouse, the infectious virus is usually absent from the peripheral organs and blood (12,13,15,16,39,42,43). However, virus replicates to high titers in the brain, and mice die 5 to 7 days after infection due to fatal encephalitis, as previously demonstrated with ZPC738 (2, 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the murine model is characterized by biphasic disease, which starts with the productive infection of lymphoid tissue and ends in the destruction of the CNS by viral replication and a "toxic" neuroinflammatory response (12,13,15,16,39,42,43). By the time encephalitis has developed in an infected mouse, the infectious virus is usually absent from the peripheral organs and blood (12,13,15,16,39,42,43). However, virus replicates to high titers in the brain, and mice die 5 to 7 days after infection due to fatal encephalitis, as previously demonstrated with ZPC738 (2, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous infection of mice leads to biphasic disease with initial replication in lymphoid tissues, followed by viremia and penetration into and infection of the central nervous system (40), where the virus replicates until death of the infected animal occurs (12,13,16,39). The infection of the CNS results in an acute meningoencephalitis that leads to the death of large numbers of neuronal cells and 100% lethality in mice (18,27).…”
mentioning
confidence: 99%
“…39 Aerosol infections of mice by VEEV have shown a tropism for the olfactory neuroepithelium, resulting in more rapid neuroinvasion relative to a subcutaneous exposure. 40,41 VEEV is able to infect a range of neuronal cell types, and lesions are observed in both neural and non-neural tissues. Use of an array of attenuated virus strains and immunodeficient mouse strains has elucidated both viral and host factors that play key roles in VEEV pathogenesis.…”
Section: Path From Experimental Vaccines To Licensurementioning
confidence: 99%
“…The nebulizer was recharged every hour with a fresh suspension to maintain the initial liquid level and to keep the viral concentration approximately the same throughout the entire procedure. Another portion of the dry, filtered air supplied at a flow rate of 10 L/min was mixed with the aerosol stream from the nebulizer before entering a 400-L dynamic test chamber, in which a horizontal aerosol flow of 0.1 m/s was established (Ryzhikov et al 1995). A total air flow of 6 + 10 = 16 L/min allowed us to create appropriate operational conditions for the chamber (such as a uniform flow) and minimize the particle losses due FIG.…”
Section: Experimental Apparatus and Protocolmentioning
confidence: 99%